Christians in the American empire : faith and citizenship in the new world order - Rougeau, Vincent D., 1963- (Oxford University Press, 2008)
What does it mean to be a Christian citizen of the United States today? This book challenges the argument that the United States is a Christian nation, and that the American founding and the American Constitution can be linked to a Christian understanding of the state and society. Vincent Rougeau argues that the United States has become an economic empire of consumer citizens, led by elites who seek to secure American political and economic dominance around the world. Freedom and democracy for the oppressed are the public themes put forward to justify this dominance, but the driving force behi.